Diet of Cattle Egrets (Bubulcus ibis ibis) in the flood valley of the Paraná River, northern Argentina - Ducommun, María de la Paz (2009)
Fil: Ducommun, María de la Paz. Instituto Nacional de Limnología (INALI, CONICET-UNL); Santo Tomé; Santa Fe